Pan-Germanism versus Christendom;: the conversion of a neutral; - Johannet, René (Hodder & Stoughton, George H. Doran company, 1917)
Preface.--I. The German hostilities in Belgium and the instructions of Benedict XV--an open letter from M. Prüm to Herr Erzberger--II. The proceedings instituted against M. Prüm.--III. Appendix: the evolution of the German Catholic Centre.